An ESIPT based naphthalimide chemosensor for visualizing endogenous ONOO− in living cells. Issue 4 (8th January 2018) - Fu, Yunshuang; Nie, Hailiang; Zhang, Rubo; Xin, Fangyun; Tian, Yong; Jing, Jing; Zhang, Xiaoling
Abstract : An ESIPT based naphthalimide chemosensor with high sensitivity and selectivity for visualizing endogenous ONOO − in living cells was developed. Abstract : Based on ESIPT, we designed and synthesized a naphthalimide chemosensor N-CBT for selectively visualizing endo/exogenous peroxynitrite (ONOO − ) in living cells. The incorporation of 2-benzothiazoleacetonitrile offers N-CBT a rare pre-existing eight-membered ring hydrogen bonding configuration, which is able to generate two types of emission of naphthalimide. Confirmed by calculation results, fast proton transfer from the hydroxyl group to the carbonyl group occurs along with excited-state energy transfer via the intramolecular H-bond, leading to a tautomeric transformation from the excited enol form to the excited keto form. In aqueous solution, the formation of intermolecular hydrogen bonding with water perturbs ESIPT and destroys the stable planar construction. By breaking the cyano carbon–carbon double bond in the presence of ONOO −, green fluorescence can be regenerated efficiently. As a result, 34-fold fluorescence enhancement at 518 nm was observed in response, and it showed a good linear relationship in the range of 1 to 14 μM with a detection limit of 37 nM. Subsequently, N-CBT was applied in visualizing cellular ONOO −, and it demonstrated great potential in selectively visualizing endo/exogenous peroxynitrite (ONOO − ) in living cells.